ABORSI DITINJAU DARI PERSPEKTIF HUKUM HINDU - Ni Ketut Kantriani; Ni Wayan Arini (VYAVAHARA DUTA, 2022)
Abortion has always been an interesting topic todiscuss from a legal perspective, both national law and religious law, especially Hindu religious law. This is due to conflicts between the Criminal Code and Law Number 36 Year 2009 concerning Health. This contradiction can be seen from Article 299, Article 346 to Article 349 of the Criminal Code which regulates and strictly prohibits abortion for any reason, religious law in Indonesia, including Hindu religious law, strictly prohibits abortion, but in Law No. allow abortion on the grounds of medical emergency indications and rape victims. In Indonesia, abortion is regulated in the Criminal Code, which is classified as a crime against life. This act of abortion is prohibited because it is not in accordance with the rights of human life, which is one of the aspects concerning the right of the fetus to live and the reproductive rights of women. All religions in Indonesia expressly prohibit abortion, especially in Hindu law, abortion is a violation of Hindu criminal law (Kantaka Sodhana), namely public law which contains legal regulations that regulate legal relations between citizens and the state concerning the public interest. Kantaka Sodhana regulates matters concerning lying (crimes against the lives of others), corah (crimes against other people's property) and paradara (crimes against decency or decency) as well as sanctions imposed on violators. Abortion in Hindu Criminal Law is included in lying (a crime against another person's life).Hindu religious law strictly prohibits the act of killing which in Hinduism is called himsa karma. Hindu law regulates the prohibition of killing living things such as animals, humans and including abortion because this act is an act of sin, this is stated in the slokantara sloka 17 which is the biggest sin (Ati Pitaka). The verse states that the biggest sins include 1) destroying holy places (temples, mosques, churches), 2) killing Brahmins, priests, and 3) abortion. From the explanation of the verse, abortion or abortion in Hindu religious law is the biggest sin.